Kotagede Heritage City: Dynamics of Urban Tourism in Kotagede Yogyakarta - Khairune Nisa, An Nuur (Jurnal Toursci, 2024)
This study aims to target Kotagede's tourist attractions, which lie in its historical and cultural heritage, including traditional houses and heritage sites, as well as performances, culinary, and art. The region's historical significance, since the establishment of the Mataram kingdom, provides a wealth of wealth for visitors to explore. Preserving traditional architecture, such as traditional wooden joglo houses and eclectic merchant houses, adds to Kotagede's appeal as a heritage city. This research uses a qualitative method approach to describe the natural condition of objects, where the researcher is the key instrument. The reason researchers choose descriptive research is to be able to describe systematically and accurately facts and characteristics about the population or a particular field. Kotagede's characteristics align with urban tourism's attributes, the first of which is connectivity. In this region, spaces between regions are connected by narrow streets and alleys of community housing. Each tourist attraction place is also equipped with signs and signs. Some roads are arranged to be one way that is useful for regulating traffic density. Furthermore, tourist activities and attractions are heterogeneous. Kotagede attracts different types of tourists with different motivations. From those who want to walk, go on a study trip, culinary to pilgrimage. In the Kotagede area, there are overlapping events between the activities of residents and tourists, such as residents shopping at the market while tourists explore culinary.